Türkiye’de Hâkim Rüzgâr Yönü Değişimleri (1931-2020) - Erkan Yılmaz; İhsan Çiçek; Sedat Avcı (Coğrafi Bilimler Dergisi)
The change in the position of the pressure system, which is one of the climatic elements, can also change the wind direction. In this study, the wind direction frequencies measured at stations of the General Directorate of Meteorology in Türkiye between 1931 and 2020 were evaluated. The 90-year period was divided into 9 sub-periods of 10 years each and 8 periods in which the change between two consecutive periods was examined. The prevailing direction changes in these periods and periods were examined, and the multiple Rubinstein prevailing wind direction method was developed and applied to 167 stations. According to the results obtained, the prevailing directions in Türkiye are constantly changing, both clockwise and counterclockwise. In the stations around Lake Van, the Marmara Sea, the Salt Lake, and the Bosphorus, the prevailing direction can change in the opposite direction, and land-sea thermal heating differences are effective in this. In the last 30 years in Türkiye, changes in the low-angle prevailing direction have occurred at some stations, and it is understood that this may be related to construction. In addition, the prevailing direction change characteristics of continuously low, continuously high, subsequently fixed, continuously growing, and continuously decreasing were determined in Türkiye, and it was observed that there were single, double, and triple cycle dominant direction changes in some stations.